Bagaimana Pengaruh Harga Emas Dunia, Harga Minyak Dunia, Dan Volatilitas Nilai tukar Terhadap Fluktuasi Harga Bitcoin Periode 2021-2023 - Ikhzal Amyza Putra; Irwan Suryadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This research was conducted to find out how the effect of world gold prices, world oil prices and exchange rate volatility on bitcoin price fluctuations in the period of oil price and exchange rate volatility on bitcoin price fluctuations in the 2021-2023 period 2021-2023. Bitcoin, which introduced in 2009, has grown to become the most popular digital asset in the world popular digital asset in the world. The method used in this research uses a quantitative approach with time series analysis method to analyse the effect of gold prices, oil prices, and Rupiah exchange rate volatility on Bitcoin price fluctuations. Bitcoin price. The sample used is secondary data obtained from trusted sources, including Bloomberg, Yahoo Finance, id.nvesting, Statistia, katadata databoks, Bank Indonesia, and cryptocurrency exchanges that provide daily data related to Bitcoin prices, gold price, oil price, and the Rupiah exchange rate against the US Dollar.  and for data analysis using multiple linear regression method which aims to see the simultaneous influence of gold prices, oil prices, and exchange rate volatility on Bitcoin price fluctuations. Bitcoin price. The research results show that partially the world gold price has a negative and insignificant effect on Bitcoin price, world oil prices show a negative and insignificant effect on bitcoin price fluctuations and exchange rate volatility. significant effect on bitcoin price fluctuations and variable exchange rate volatility exchange rate volatility variable shows an insignificant positive effect on bitcoin price fluctuations. bitcoin. Simultaneously the three independent variables, namely the world gold price, world oil price, and exchange rate volatility. world price, world oil price, and exchange rate volatility have no significant effect on the dependent variable on the dependent variable Bitcoin price.